Analisa Pengaruh Waktu Aerasi Terhadap Penurunan Kadar Zat Besi (Fe) Dalam Pengolahan Air Bersih - Sitorus, Boris Habibullah; Andayani, Ratih Diah; Afriany, Reny (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Gran serra housing in Palembang is one of the aeras that has not yet received clean water supply from the local water utility (PDAM). To meet daily water needs, residents rely on dug well water containing iron (Fe) at a concentration of 1,15 mg/L. this study aims to analyze the effect of aeration time variation on the reduction of iron content using the aeration-filtration method. During the aeration process, hydraulic parameters such as flow rate, velocity, Reynolds number, head loss, and loss coefficient were calculated. Aeration was carried out for 45 and 75 minutes, followed bya a filtration process. The results showed that after 45 minutes of aeration-filtration, iron content decreased to 0,92 mg/L (a 3% reduction), and after 75 minutes, it decreased to 0,37 mg/L (a 68% reduction). The aeration process yielded a flow rate of 0,000328 m3/s, velocity of 2,549508284 m/s, Reynolds number of 40.550563, head loss of 2,04204 and loss coefficient of 6,15755. These findings demonstrate that 75 minutes of aeration followed by filtration is effective in reducing iron levels in well water.